An unusual presentation of a reno-pleural fistula. (January 2014) - Nilsen-Nunn, A; Beckley, I; Wah, T; Cartledge, J; Joyce, A
The management of small renal cell carcinomas in Von Hippel Lindau (VHL) syndrome involves nephron-sparing techniques. The authors report a case of a reno-pleural fistula presenting two years' post-radiofrequency ablation. Pathophysiological mechanism and patient education are explored.